Effect inoculation soil and sweet corn seeds with Pseudomonas fluorescens and Azospirillum lipoferum on solubilizing some forms of fixed phosphorus in soil - كبيبو, عيسى; بدران, أمجد; حليبيه, مها (Latakia University Journal -Biological Sciences Series, 2021)
The research was carried out at Alsnobar research station in Lattakia in June in 2019. Inoculation soil and seeds of sweet maize (Fyhaa) was conducted with Pseudomonas fluorescens (bacteria solubilizing phosphate) and Azospirillum lipoferum (bacteria fixing nitrogen) individually and together. The inoculation was at increasing levels of nitrogen and phosphorus fertilizer needs. The levels of nitrogen and phosphorus fertilizers was (1, 2, 3, 4, 5) which equal (0:0, 137:107, 183:143, 227:177, 273: 213) kg N:P2O5/hectare. The results indicated that the amount of phosphorus fixed on Al and Fe components was decreased by inoculation by Pseudomonas fluorescens and Azospirillum lipoferum individually by percent of (10.7 to 76.7)% and (12.2 to 86.4)% according to control treatments at different fertilizer levels. The inoculation with two bacterial species (Pseudomonas fluorescens and Azospirillum lipoferum) do not cause any significant difference in Ca-P.